DRIVERS & OUTCOMES OF HUMAN CAPITAL ANALYTICS - Faiz, Misbah (PEOPLE: International Journal of Social Sciences, 2024)
The current article analyzes human capital analytics and develops a model for the drivers and outcomes of human capital analytics. A total of 81 articles have been analyzed using content analysis and a model has been developed for drivers and outcomes of human capital analytics. The model identifies four drivers and seven outcomes of human capital analytics. The drivers include organizational culture, employee hard & soft skills, employee competencies and skilled workforce. The outcomes include stronger inter-departmental relationships, improved employee experience and behavior, knowledge-based decisions, improved company performance, provision of competitive edge, risk reduction and enhancement of strategic organizational capability. We see that human capital analytics is an emerging phenomenon and yet much literature does not exist on the phenomenon. Considering minimal exploration of HR data analytics and its hidden role in the company’s performance, the area has been less approached. Our review addresses the mentioned shortcomings and provides a roadmap for future research.